Pediatric Sports Medicine, A New Subspeciality in Orthopedics: An Analysis of the Surgical Volume of Candidates for the American Board of Orthopaedic Surgery Part II Certification Exam Over the Past Decade. Issue 1 (January 2019) - Obey, Mitchel R.; Lamplot, Joseph; Nielsen, Ena D.; Andras, Lindsay M.; Mignemi, Megan; Sawyer, Jeffrey; Flynn, John M.; Albanese, Stephen A.; Hosseinzadeh, Pooya
Abstract : Background: Pediatric orthopaedic surgery has become increasingly subspecialized over the past decade. The purpose of this study was to analyze the volume of pediatric sports medicine cases performed by surgeons applying for the American Board of Orthopaedic Surgeons (ABOS) Part II certification exam over the past decade, comparing caseloads according to the type(s) of fellowship completed. Methods: The ABOS database was reviewed for all surgeons applying for the ABOS Part II certification exam from 2004 to 2014. Fellowship training of the candidates was recorded as Pediatrics, Sports, and Dual-Fellowship (fellowship in both Pediatrics and Sports). All other candidates were categorized as "Other". A total of 102, 424 pediatric cases (patients below 18 years) were reviewed to identify sports medicine cases performed by CPT code. Multiple linear regression and Mann-Whitney U tests were used to determine trends in case volume overall and according to fellowship training for all patients, patients ≥13 and patients <13. One-way ANOVA testing was used to compare multiple means followed by multiple post hoc comparisons using a Tukey all pairwise approach using SPSS. Results: A total of 14, 636 pediatric sports medicine cases were performed. There was an increase in the number of sports medicine cases performed in patients <13 (117.5±31.8 from 2004-2009 to 212.4±70.1 from 2010-2014, P =0.035; r 2 =0.743, P =0.0007). The number of Pediatrics ( r 2 =0.601, P =0.005), Sports ( r 2 =0.741, P =0.0007) and Dual-Fellowship candidates increased ( r 2 =0.600, P =0.005) from 2004-2014. Dual-Fellowship surgeons performed 21.4% of pediatric sports medicine cases in 2014 when compared to 2.1% in 2004 (919% increase). As a group, the number of pediatric sports cases performed by Dual-Fellowship ( r 2 =0.630, P =0.004) and Sports ( r 2 =0.567, P =0.007) candidates has increased, while the number performed by "Other" candidates has decreased ( r 2 =0.758, P =0.0005). Per surgeon, Dual-Fellowship candidates performed a greater number of pediatric sports cases per collection period (36.5±9.18) than Pediatrics (6.71±0.94), Sports (5.99±0.46), and "Other" (1.21±0.15, P <0.0001 for each) candidates from 2004 to 2014. Conclusions: Over the past decade operative sports injuries have increased in children with a similar increase in the number of orthopedic surgeons specializing in pediatric sports medicine. On a per surgeon basis, these dual fellowship-trained candidates have performed on average five times the number of pediatric sports medicine cases compared to all other ABOS Part II candidates. These trends may point towards the development of a new subspecialty of pediatric sports medicine among orthopedic surgeons. Level of Evidence: Level IV— Retrospective Database Review. Abstract : Supplemental Digital Content is available in the text.